Perspektywy rozwoju tłumaczenia maszynowego (na przykładzie angielsko-rosyjskich relacji przekładowych) - Olas, Jakub (Studia Rossica Posnaniensia, 2019)
Machine translation (MT) is a relatively new field of science. MT systems are evolving in certain directions. The article discusses the possibilities and the future of systems currently offered to public by the biggest technological companies focusing on English-Russian translation relations.